Chlorophyll Breakdown – How Chemistry Has Helped to Decipher a Striking Biological Enigma - Kräutler, Bernhard (Synlett, 2019)
How the fall colors arise and how chlorophyll (Chl) breakdown occurs in higher plants has remained enigmatic until three decades ago. Fundamental insights into this fascinating puzzle have been gained, meanwhile, by basic contributions from plant biology and chemistry. This short review is a personal account of key advances from synthetic, mechanistic, and structural chemistry that led to the discovery of the bilin-type Chl catabolites and helped elucidate the metabolic processes that generated them from Chl.1 Introduction2 Discovery and Structure Elucidation of a First Non-Green Chl Catabolite3 Structure Elucidation of Fleetingly Existent Blue-Fluorescent Chl Catabolites4 The Red Chl Catabolite – Key Ring-Opened Tetrapyrrole Accessed by Partial Synthesis5 Synthesis of ‘Primary’ Fluorescent Chl Catabolites by Reduction of Red Chl Catabolite6 Nonfluorescent Chl Catabolites from Isomerization of Fluorescent Chl Catabolites7 Persistent Fluorescent Chl Catabolites and Blue-Luminescent Bananas8 Discovery, Structure Elucidation, and Biological Formation of Dioxobilin-Type Chl Catabolites9 Occurrence, Partial Synthesis, and Structure of Phyllochromobilins, the Colored Bilin-Type Chl Catabolites10 Conclusion and Outlook
Keywords: antioxidants; bilin; catabolite; chlorophyll; fluorescence; glycoside; heterocycles; pigments; porphyrinoids; phyllobilin; senescence; tetrapyrroles